Application of Flexible AC Transmission System Devices in Wind Energy Conversion Systems - Abu-Siada, Ahmed; Shahnia, F.; Yunus, A. (Bentham Science Publishers, 2017)
This book presents information about the application of various flexible AC transmission system devices to wind energy conversion systems.